Enzymatic Synthesis of Sialyl Lactosamine Grafted Chitooligosaccharides. Issue 11 (23rd March 2023) - Yan, Jun; Li, Jianghua; Hu, Zhifei; Ma, Xiaoyao; Li, Yun; Hu, Xihuan; Ye, Jinfeng; Wang, Wei; Wan, Renzhong; Cao, Hongzhi
Comprehensive Summary: An efficient enzymatic assembly strategy was developed for the concise synthesis of structurally well‐defined sialylated chitooligosaccharides. Two enzyme modules for the β‐1, 3‐ N ‐acetyl‐glucosaminylation and β‐1, 4‐galactosylation were applied for the grafting N ‐acetyl lactosamine (LacNAc) unit(s) onto the chitooligosaccharides. The LacNAc grafted chitooligosaccharides were further modified with α‐2, 3‐ or α‐2, 6‐sialylation by two enzymatic sialylation modules to generate a total of 20 sialylated chitooligosaccharides. The inhibition study of influenza virus‐induced cytopathy with synthetic sialylated chitooligosaccharides indicated that the sialic acid linkage and chain length both contribute to the binding preference and inhibition potency. Abstract : An efficient enzymatic assembly strategy was developed for the concise synthesis of structurally well‐defined sialylated chitooligo‐saccharides. Two enzyme modules for the β‐1, 3‐ N ‐acetyl‐glucosaminylation and β‐1, 4‐galactosylation were applied for grafting N ‐acetyl lactosamine (LacNAc) unit(s) onto the chitooligosaccharides. The LacNAc grafted chitooligosaccharides were further modi‐fied with α‐2, 3‐ or α‐2, 6‐sialylation by two enzymatic sialylation modules to generate a total of 20 sialylated chitooligosaccharides. The inhibition study of influenza virus‐induced cytopathy with synthetic sialylated chitooligosaccharides indicated that the sialic acid linkage and chain length both contribute to the binding preference and inhibition potency.